Identification of an isomer impurity in piperaquine drug substance. - Lindegårdh, N; Giorgi, F; Galletti, B; Di Mattia, M; Quaglia, M; Carnevale, D; White, N; Mazzanti, A; Day, N (2006)
A significant contaminant of the antimalarial drug piperaquine (1,3-bis-[4-(7-chloroquinolyl-4)-piperazinyl-1]propane) has been identified using liquid chromatography-mass spectrometry (LC-MS) and 2D NMR spectroscopy (1H-1H COSY, 1H-13C HSQC, 1H-13C HMBC). The impurity was identified as the positional isomer 1-[(5-chloroquinolin-4)-piperazinyl]-3-[(7-chloroquinolin-4)-piperazinyl]propane. The impurity is formed because of contamination of batches of 4,7-dichloroquinoline (a precursor in the synthesis of piperaquine) with 4,5-dichloroquinoline. The amount of impurity (peak area impurity/peak area piperaquine using LC-UV at 347 nm) in old batches of piperaquine and in Artekin (the combination of dihydroartemisinin-piperaquine) ranged from 1.5 to 5%.